Accumulation studies at specific sampling areas of the active floodplain in the Upper-Tisza region - Molnár, Gábor; Scholtz , Andor; Vass, Róbert (Acta Geographica Debrecina Landscape & Environment series, 2017)
In this paper the rate of accumulation was studied along four VO floodplain cross sections of the UpperTisza region between 1974 and 2014. VO floodplain cross sections are based on a mapping base-point grid (established in 1890), and they are located a few kilometers from each other. Furthermore, the roughness changes of different surface types, crossed by the VO floodplain cross-sections, were also determined between 1965 and 2015. The accumulation studies were extended to include the accumulation rates of the cut off meanders located along and/or close to the VO cross-sections. The roughness values increased in all four floodplain VO cross-sections since 1965; in two of them it reached or approximated 100 %. The average accumulation along the VO cross-sections was between 28 and 47 cm (0.73–1.23 cm/year) during the 38-year period. However, its areal distribution showed large differences. The highest values (169–309 cm, i.e. 4.44–8.13 cm/year) were found at the lowest points of the cut off meanders and swales in every case. The accumulation rate of the examined three cut off meanders near the floodplain cross-sections (140 and 1570 meters from the river bed) was lower (0.84–2.5 cm/year), but the study period was significantly longer (154 and 161 years, respectively). Comparing the values of the two periods, it is obvious that the accumulation of the active floodplain accelerates, presumably due to the significant increase of surface roughness.